Evaluation of black soldier fly larvae oil as a dietary fat source in broiler chicken diets - Byeonghyeon Kim; Han Tae Bang; Ki Hyun Kim; Min Ji Kim; Jin Young Jeong; Ju Lan Chun; Sang Yun Ji (Journal of Animal Science and Technology, 2020)
The present study was conducted to evaluate the effects of black soldier fly larvae oil (BSFLO) from the black soldier fly larvae (BSFL) as a partial or total replacement of soybean oil (SBO) on growth performance, fatty acid (FA) profile, and meat quality of broiler chickens from 1 to 5 wk of age. A total of 210 male broiler chickens (Ross 308) at one-day of age were randomly allotted to 3 dietary treatments (10 replicates and 7 birds/group): a basal control diet (CON), the basal diet in which the SBO was replaced by 50% (50 BSFLO) or 100% (100 BSFLO) of BSFLO. The growth performance, physical measurements and chemical traits of leg meat, and sensory analysis of breast meat were not influenced by diets. However, the relative weight (g/kg) of gizzard of CON was significantly higher (14.85, 12.52, and 13.02 for CON, 50 BSFLO, and 100 BSFLO; p < 0.05) than that of other treatments. As expected, the FA profile of breast meat was affected by BSFLO inclusion. The proportion (%) of saturated fatty acid (SFA) was increased (27.16, 27.58, and 28.72 for CON, 50 BSFLO, and 100 BSFLO; p < 0.05) by BSFLO inclusion and the percentage (%) of MUFA was also increased (43.36, 44.58, and 48.55 for CON, 50 BSFLO, and 100 BSFLO; p < 0.01). On the contrary, the proportion (%) of PUFA was decreased (29.49, 27.84, and 22.74 for CON, 50 BSFLO, and 100 BSFLO; p < 0.01). In conclusion, the present study suggests that the replacement of BSFLO did not show an adverse effect on growth performance and it could be an ingredient as a dietary fat source for a broiler diet.